Cardiac involvement in Kawasaki disease in Pakistani children - Saleem Akhtar; Muhammad Matloob Alam; Mehnaz Atiq Ahmed (Wolters Kluwer Medknow Publications, 2012)
Introduction: Coronary artery involvement is the most dreaded long-term complication of Kawasaki disease. Our aim was to look at the pattern of cardiovascular involvement in Pakistani children admitted with Kawasaki disease. Methods: This study included children admitted with Kawasaki disease at the Aga Khan University Hospital Karachi over a period of 14 years from January 1997 to December 2010. Information gathered included patient demographics, clinical features, investigations, echocardiographic findings, treatment and follow-up. Those with coronary artery involvement on initial echocardiogram remained on long-term follow-up with clinical examination and echocardiogram. Results: A total of 56 patients were admitted. (Mean age at diagnosis 33 ± 30 months, age range 2 months to 9 years). 18% of patients had incomplete features. Twenty-five percent (14/56) patients presented after 10 days of fever. Cardiac examination was normal except for tachycardia. Abnormal coronary arteries were seen in 23 patients (41%) - left main coronary artery in 23 (41%), left anterior descending and right main coronary artery in 20 (36%), circumflex branch in 17 (30%). Risk factors for cardiac involvement were male sex, fever >10 days duration at the time of initial presentation and neutrophil percentage >75% in the initial white blood cell counts. Fifty four of 56 cases received intravenous immunoglobulin (IVIG), Seventy-five percent of the patients received IVIG within 10 days of illness. Mean duration of follow-up was 2.5 years. Eight percent of the patients still continue to have abnormal coronaries. There was no mortality. Conclusions: A higher incidence of coronary artery involvement was found in our study. Presentation after 10 days of illness increases the risk of coronary artery involvement. High index of suspicion among the general pediatricians about the disease can possibly be helpful for early referral and treatment.